A Survey of the Vision of Future the Members of the Football Academies have at the Academies in the Capital City and in the Provinces - Rábai, Dávid (Central European Journal of Educational Research, 2022)
Although research into various dimensions of Hungarian football academies has become more intensive over the recent years, there is still a wide range of questions and problems to be addressed, most of which can be identified in the educational-pedagogical dimensions of the academies. Our present research concentrates on the players of 3 academies in the provinces and 3 in the capital city (N=560). As a method of the research, we opted to use an inventory to collect the answers of the players (Rábai, 2021). We interviewed them about the way they imagine their future and their responses were, at each question, analysed in a comparison of the provinces and the capital. We assumed that there were considerable differences between the two groups, based upon the review and findings of the relevant literature. We found significant differences between the answers of the players of the two groups of academies, primarily in the aspirations to achieve vocational qualifications (p=0,039), the students’ views about their prospects of a professional career (p=0,000) and a career abroad (p=0,047) (Rábai, 2021). Our findings suggest that the majority of the young football players we contacted have a largely positive vision of their future. It especially applies to the students of academies in the capital city. In a number of their responses, students in the capital city provided answers that were highly confident.